2021
DOI: 10.3389/fpubh.2021.700401
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Screen Exposure During COVID-19—The Brain Development and Well-Being Concerns of Our Younger Generation

Abstract: COVID-19 is a significant public health crisis and it has given a major impact especially in the field of education. The situation has forced educators around the world to shift to an online mode of teaching and children are forced to study online at home. The benefits of online learning are undeniable, but the possible long-term developmental risks of prolonged screen use should not be overlooked. Recent research findings have clearly suggested the negative effects of screen time on the brain development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In parallel to the teaching medium being shifted, the learning medium for young people also changed. From a face-toface medium, the shift often moved to that of a screen [25]. Whilst a screen for some may have been quite large, for others it would have been much smaller, perhaps the size of a smartphone screen [26].…”
Section: Review Of Appropriate Literaturementioning
confidence: 99%
“…In parallel to the teaching medium being shifted, the learning medium for young people also changed. From a face-toface medium, the shift often moved to that of a screen [25]. Whilst a screen for some may have been quite large, for others it would have been much smaller, perhaps the size of a smartphone screen [26].…”
Section: Review Of Appropriate Literaturementioning
confidence: 99%
“…Recent research has clearly explained that there are some health risks associated to screen time. Wong [30] found that e-learning requires time but has some risk factors attached to an individual's health, that is, brain development and well-being.…”
Section: Prolonged Screen Exposure Can Lead To Health Problemsmentioning
confidence: 99%
“…As dificuldades encontradas foram inúmeras e, muito frequentemente, não superadas, a julgar pelos primeiros números disponíveis referentes à alfabetização (BID et al, 2021a;Todos pela Educação, 2021a). Para o desenvolvimento das atividades remotas, por exemplo, o meio que pareceria ideal, as plataformas de ensino a distância -pois permitem a interação de todos, estudantes e professores -é um recurso indisponível para muitos, desprovidos dos equipamentos e da infraestrutura necessárias (Rolon et al, 2021), além de inoportuno, especialmente para as crianças da educação infantil ou em idade de alfabetização, devido ao tempo demasiadamente longo de exposição a telas (Singh e Balhara, 2021;Wong, 2021).…”
Section: Igualdade Racialunclassified